Clinical Perspectives on Range of Motion in Orthopedic Conditions - Soni, Jaykumar D.; Patel, Niketa (Medical Science: Trends and Innovations Vol. 5, 2025)
Orthopedic conditions such as osteoarthritis, rotator cuff injuries, and ligament tears are commonly associated with restrictions in Range of motion (ROM). These limitations can lead to joint stiffness, pain, and altered biomechanics, often resulting in compensatory movements that increase the risk of secondary injuries. In therapeutic contexts, restoring and optimizing ROM is a primary goal. Rehabilitation programs, including physical therapy and manual techniques, aim to enhance joint mobility, improve functional capacity, and reduce the risk of complications such as contractures or muscle imbalances. This review aims to explore clinical methods of measuring range of motion, the role of clinical observation and patient-reported outcomes, reliability and validity of ROM assessment tools and interventions related to a range of motion in orthopedic conditions to improve patient outcomes.